The Invention of the Countryside - Landry, Donna. author. aut Link
XX, 306 p.
Keywords: Today's hunting debate began in the eighteenth century, when the idea of the countryside was being invented through the imaginative displacement of agricultural production in favour of country sports and landscape tourism. Between the Game Act of 1671 and its repeal in 1831, writers on walking and hunting often held opposed views, but contributed equally to the origins of modern ecology, while sharing a commitment to trespass that preserved common rights in an era of growing privatization.